The Classroom Character Education in English Lessons Based on the 2013 Curriculum - Putu Mila Romana Dewi (Indonesian Journal Of Educational Research and Review, 2021)
The morality and character of the Indonesian nation are decreasing. This is evidenced by many cases of violence, sexuality, drugs, cybercrime, bullying. Some students also commit deviant actions such as cheating and smoking. This study aims to analyze the practice of character education in learning English. This type of research is qualitative. The methods used to collect data are observation, interviews, and questionnaires. The instruments used in this study were interview guides, note-takers, lesson plan analysis checklists, and observation checklists. The technique used to analyze the data is descriptive qualitative analysis. The results showed that the teacher had inserted the character values in the lesson plans contained in the indicators, learning materials, learning steps, assessment instruments, and the teaching and learning process. Furthermore, learning topics and indicators affect the differences in character values contained in the learning process. While the assessment of character education in the teaching and learning process used by the teacher is an investigation in the form of an advice and assessment rubric. This research implies that teachers can instill character values in students so that they can form superior student characters.